PENGARUH HAMBATAN SAMPING TERHADAP KINERJA JALAN (STUDI KASUS: JALAN PELITA DAN JALAN FLAMBOYAN, JALAN SEKITAR TAMAN SANGKAREANG, KOTA MATARAM) - I PUTU RAKA ASTAWA; MADE MAHENDRA; I GEDE PUTU WARKA (GANEC SWARA, 2023)
Some traffic problems often arise due to an activity from the side of the road segment. Congestion is a problem that often occurs in urban road traffic. Congestion is caused by a lack of ability or capacity of the road to provide services to the volume of vehicles crossing a certain road section as well as the presence of high side friction conflicts that cause vehicle speeds to slow down which results in a non-smooth traffic flow.Sangkareang Park is one of the areas located in the center of Mataram City which is a public facility for the community. This resulted in an increase in side barriers on roads around Sangkareang Park. This study aims to determine the value of side friction and road performance on roads around Sangkareang Park, namely Jalan Flamboyan and Jalan Pelita. Furthermore, this research was conducted to determine the effect of the side friction on road performance as described by speed and degree of saturation.The results of the study on the Flamboyan road section had the highest side resistance, speed, and degree of saturation values of 814.8 incidents/hour, 32.53 km/hour, and 0.09. On the Pelita road, the highest values of side resistance, speed, and degree of saturation were 1614.6 incidents/hour, 30.90 km/hour, and 0.16 respectively. The results of the simultaneous regression analysis found that the side resistance affects the speed and degree of saturation. The results of the partial regression analysis show that on the Flamboyan road, the side friction variable that has the most influence on speed and degree of saturation is Slow Vehicles (SMV) while on Pelita road, the side resistance variable that has the most effect on speed and degree of saturation is vehicles entering and leaving (EEV). ) followed by the parking and stopping vehicle variable (PSV).